Improving Cancer Related Fatigue Management through Ergonomic Workshops - Nurhesti, Putu Oka Yuli; Adiputra, Nyoman; Adiatmika, Putu Gede; Tirtayasa, Ketut (Journal of A Sustainable Global South; Vol 7 No 1 (2023): February 2023, 2023)
The ergonomics workshop on Cancer Related Fatigue (CRF) management is a method for designing an ergonomic approach to meet the physical and psychological needs of breast cancer patients who experience CRF and return to work. Through workshops, improvement of work procedures can be carried out in a comprehensively because it involves the participation of all components involved in the approach to be carried out. The purpose of this research is to get the best working procedures for CRF management and to analyze the knowledge of the respondents before and after the workshop. This is a quantitative study with a pre and post-test approach. Focus Group Discussions are conducted to collect data. Workshops for handling CRF in breast cancer patients who return to work are carried out by involving oncology nurses, oncologists, ergonomic experts, nutritionists, health sciences students and breast cancer patients who return to work and heads of work units. Respondents were divided into 3 groups and 12 stages of the workshop were carried out. The results show that work comfort, programs that facilitate physical activity and being able to meet cancer sufferers, work attitudes, physical activity, social support are expected components of work procedures. Respondents' knowledge before and after the workshop differed significantly with p=0.0001. This workshop can help increase patient and healthcare workers' knowledge about CRF and help find the best therapy and work procedures for CRF management. Keywords: workshop, ergonomics, cancer related fatigue